Making sense of scattering: seeing microstructure through shear waves - Annio, Giacomo; Holm, Sverre; Mangin, Gabrielle; Penney, Jake; Bacquët, Raphael; Mustapha, Rami; Darwish, Omar; Wittgenstein, Anna Sophie; Schregel, Katharina; Vilgrain, Valérie; Paradis, Valérie; Sølna, Knut; et al. (Science advances, 2024)
The physics of shear waves traveling through matter carries fundamental insights into its structure, for instance, quantifying stiffness for disease characterization. However, the origin of shear wave attenuation in tissue is currently not properly understood. Attenuation is caused by two phenomena: absorption due to energy dissipation and scattering on structures such as vessels fundamentally tied to the material’s microstructure. Here, we present a scattering theory in conjunction with magnetic resonance imaging, which enables the unraveling of a material’s innate constitutive and scattering characteristics. By overcoming a three-order-of-magnitude scale difference between wavelength and average intervessel distance, we provide noninvasively a macroscopic measure of vascular architecture. The validity of the theory is demonstrated through simulations, phantoms, in vivo mice, and human experiments and compared against histology as gold standard. Our approach expands the field of imaging by using the dispersion properties of shear waves as macroscopic observable proxies for deciphering the underlying ultrastructures.
Veröffentlicht: 31. Juli 2024
Gesehen am 18.08.2025